The monitoring of H 2S and SO 2 noxious gases from Industrial environment with sensors based on flame-spray-made SnO 2 nanoparticles - Chaikarn Liewhiran (2018)
The noxious gas sensors were developed successfully using flame-spray-made SnO 2 nanoparticles as the sensing materials. The functionalized nanoparticle properties were further analyzed by XRD, BET and TEM analyses. The SnO 2 nanoparticles (SSA BET: 141.6 m 2/g) were investigated revealing non-agglomerated spherical, hexagonal, rectangle (3-10 nm), and rod-like (3-5 nm in width and 5-20 nm in length) morphologies. The sensing films were prepared by spin coating onto the Al 2O 3 substrates interdigitated with Au electrodes. The sensing films were significantly developed in order to detect with H 2S (0.5-10 ppm) and SO 2 (20-500 ppm) at the operating temperature ranging from 200-350°C. After sensing test, the cross-section of sensing film was analyzed by SEM analyses. It was found that SnO 2 sensing film showed higher sensitivity to H 2S gas with very fast response at lower concentrations (3s, to 10 ppm). The cross sensitivities of the sensor towards different concentrations of H 2S, CO, H 2, and C 2H 2 were measured at 300°C. The sensor evidently shows much less response to CO, H 2, and C 2H 2 than to H 2S indicating higher selectivity for H 2S of the SnO 2 sensor at the lower concentration (10 ppm). Therefore, the SnO 2 sensor was the most suitable candidate for the efficient detection of H 2S noxious gas.